DATABASE MANAGEMENT SYSTEM PT SIERAD PRODUCE Tbk DI MEDAN - Sri Widya Harahap; Azizah Anisa; Siti Nuraini Pane; Muhammad Arief Rahmadiansyah Purba (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
In the current era of globalization, management information systems play a very important role where information systems cannot be realized without database processes because the two are related. The use of databases is very important because it involves computer processing which basically contains two components, namely data and instructions (programs). A database management system (DBMS) is software (program) that organizes, classifies and also displays stored data in a database using various applications. The purpose of this research is to solve several problems related to data security, concurrency and events that are good and appropriate at Pt Sierad Produce. The method used in this research is a qualitative method of seeking comprehensive information from the database management system library information sources books, articles and other library sources. The result of this research is PT Sierad Product can overcome information security problems with information security methods of information, electronic security, physical security and procedural security in data processing and minimize vulnerabilities.